ANALISIS RANTAI NILAI ( VALUE CHAIN ) PADA PRODUK BATIK TULIS DI SURAKARTA - Mangifera, Liana (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This study aims to analyze the activities of the value chain on batik products in Kampung Batik Laweyan Surakarta, to determine and identify any activity of the batik tulis products that has the highest economic value added in Kampung Batik Laweyan Surakarta, so able to increase competitive advantage. This study used a mixed approach Method, Which is a combination of qualitative and quantitative approaches. The qualitative approach used was conventional content analysis. The process of data analysis performed in this study is to analyze the content of the interview and questionnaire. Data analysis methods used in this research is descriptive statistical and Content Analysis. The results showed that the primary activities of the value chain on batik tulis products in Kampung Batik Laweyan Surakarta include: (1) Purchase of raw materials and major equipment such as fabric, waxes, dyes, and equipment. (2) The production process, including making motive, making the pattern on the fabric, bold patterns using âcantingâ, coloring, washing the fabric, shed the wax by dipping in hot water, drying the fabric to dry and display batik cloth, ( 3) Sales of the product. Selling batik usually through wholesalers both domestically and abroad, retail and end consumers. While the main activity of theÂ  batik tulis products that has the highest economic value added in Kampung Batik Laweyan is the marketing and sales